2004
DOI: 10.1093/ajcn/79.6.1199s
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory properties of conjugated linoleic acid

Abstract: In vitro studies of the use of immune cells and animal models demonstrate that conjugated linoleic acid (CLA), a lipid, modulates immune function. In addition, recent publications demonstrate that 2 active CLA isomers (ie, cis-9,trans-11 CLA and trans-10,cis-12 CLA) modulate immune function in humans. Aspects of both the innate and adaptive immune responses are affected by dietary CLA supplementation. CLA consists of a mixture of isomers, which reduced immune-induced wasting and enhanced ex vivo lymphocyte pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
162
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(167 citation statements)
references
References 44 publications
2
162
1
2
Order By: Relevance
“…This isomer is the most biologically active conjugated linoleic acids isomer and has positive effect on preventing cancer, cardiovascular disease, diabetes and immune system (Pariza et al 2001, Lock et al 2004, O'Shea et al 2004, Terpstra 2004). …”
Section: Resultsmentioning
confidence: 99%
“…This isomer is the most biologically active conjugated linoleic acids isomer and has positive effect on preventing cancer, cardiovascular disease, diabetes and immune system (Pariza et al 2001, Lock et al 2004, O'Shea et al 2004, Terpstra 2004). …”
Section: Resultsmentioning
confidence: 99%
“…The latter has been implied in inflammatory bowel disease (O'Shea et al 2004, Bassaganya-Riera and Hontecillas 2010). Linoleic acid and cis-9, trans-11 CLA isomer had no detectable effects on lipopolysaccharide (LPS)-induced TNF alpha production in cultured bovine blood.…”
Section: Cla and Immune Responsementioning
confidence: 99%
“…It has been reported that CLA up-regulates the humoral function by increased IgG, IgM and IgA production of spleen lymphocytes in a dose -dependent manner and reduces macrophage function by decreasing synthesis of inflammatory mediators and/or inflammatory enzymes (O'Shea et al 2004). CLA also reduces IgE (as well as PGE2 and IL-12) which plays a crucial role in type-I allergic reactions (Sugano et al 1998).…”
Section: Cla and Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…CLA has many important properties that regulate physiological and metabolic responses, for example, immune modulation, anti-cancer effects, prevention of cardiovascular disease and diabetes, and weight control (Ip et al, 1991;Houseknecht et al, 1998;Islam et al, 2010;Eftekhari et al, 2013;Kim et al, 2013). In animal production, studies on the effects of CLA on immune function have thus far been conducted in the normal physiological status or inflammatory challenge status (O'Shea et al, 2004;Lai et al, 2005;Zhang et al, 2005;Renner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%